Structural Restoration of Carbonate Platform in the Southern Part of Central Luconia, Malaysia - Jamaludin, S.N.F. (China University of Geosciences, 2018)
Carbonates of Central Luconia, Malaysia, had been serving as hydrocarbon reservoirs for more than 25 years. However, the relationship and impacts of extensive tectonic events to the growth of Miocene carbonates in Central Luconia have not been revealed sufficiently. In this work, two carbonates platforms in the southern part of Central Luconia were used for detailed interpretation and seismic based structural restoration. This work had provided new insight for the interpretation of carbonate growth in Central Luconia and its association with the surrounding tectonic. This work suggested three possible tectonic evolutions from Late Oligocene to Pliocene are responsible for the growth of carbonates in Central Luconia. These stages are equivalent with pre-carbonate stage (Late OligoceneâEarly Miocene), syn-carbonate stage (MiddleâLate Miocene) and post-carbonate stage (Pliocene). Rifting of the South China Sea and subduction of proto-South China Sea are believed to be responsible for the development of faulting during pre-carbonate stage, while movement of the ancient Baram Line is thought to control the parallel striking direction of normal faults during syncarbonate stage. Finally, subsidence and compaction due to the overburden clastic materials from the prograding deltas is considered as the main reason for the impacts of gravitational tectonics in this area, which corresponding to the post-carbonate stage. Â© 2017, China University of Geosciences and Springer-Verlag GmbH Germany, part of Springer Nature.